2021
DOI: 10.1074/jbc.ra120.013623
|View full text |Cite
|
Sign up to set email alerts
|

Local Myo9b RhoGAP activity regulates cell motility

Abstract: To migrate, cells assume a polarized morphology, extending forward with a leading edge with their trailing edge retracting back toward the cell body. Both cell extension and retraction critically depend on the organization and dynamics of the actin cytoskeleton, and the small, monomeric GTPases Rac and Rho are important regulators of actin. Activation of Rac induces actin polymerization and cell extension whereas activation of Rho enhances acto-myosin II contractility and cell retraction. To coordinate migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…The RHOA/ROCK pathway controls cell migration and other cell functions, mediating the nuclear localization of transcription factors or through direct regulation of the activity of transcription activators by phosphorylation, allowing actin polymerization. MYO9B is a Rho GTPase-activating protein that has four binding sites for myosin light chains, and its function is the local inhibition of RHO activity to enhance directional cell migration ( 33 ). Deletion of MYO9B in leukocytes impairs cell migration through increased Rho activity ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RHOA/ROCK pathway controls cell migration and other cell functions, mediating the nuclear localization of transcription factors or through direct regulation of the activity of transcription activators by phosphorylation, allowing actin polymerization. MYO9B is a Rho GTPase-activating protein that has four binding sites for myosin light chains, and its function is the local inhibition of RHO activity to enhance directional cell migration ( 33 ). Deletion of MYO9B in leukocytes impairs cell migration through increased Rho activity ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…MYO9B is a Rho GTPase-activating protein that has four binding sites for myosin light chains, and its function is the local inhibition of RHO activity to enhance directional cell migration ( 33 ). Deletion of MYO9B in leukocytes impairs cell migration through increased Rho activity ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“… 19 Interestingly, when MYO9B gene expression was deficient or the C-terminal dominant-negative tail expression was lacking, damaged intestinal epithelial cell line Caco2 (BBe) was unable to migrate to the wound surface, indicating the destruction of TJ proteins, as well as the decreased torsional motor ability and connection permeability. 20 This suggested that MYO9B played a crucial role in epithelial wound healing and TJ integrity maintenance, key functions that may be altered in related IBD patients. The MYO9B gene is also involved in the pathogenesis and development of IBD, and its genetic variation may affect the tight connection and assembly of epithelial cells and remodeling of the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed the percutaneous resistance of KO ileum to wild-type (WT) ileum and found that the percutaneous resistance of KO ileum was three times smaller compared with WT ileum, and the intestinal mucosa was also permeable to high-molecularweight glucan, suggesting that the impaired mucosal barrier function and the change in intestinal permeability of KO mice may have been due to the presence of mucosal 19 Interestingly, when MYO9B gene expression was deficient or the C-terminal dominant-negative tail expression was lacking, damaged intestinal epithelial cell line Caco2 (BBe) was unable to migrate to the wound surface, indicating the destruction of TJ proteins, as well as the decreased torsional motor ability and connection permeability. 20 This suggested that MYO9B played a crucial role in epithelial wound healing and TJ integrity maintenance, key functions that may be altered in related IBD patients. The MYO9B gene is also involved in the…”
Section: Dovepressmentioning
confidence: 99%
“…The motor domain directs its associated RhoGAP domain to regions of dynamic actin filaments such as for example, extending lamellipodia and filopodia, 8 allowing for local inhibition of RhoA activity in these regions by Myo9b. 9 Active RhoA regulates the organization of the actin cytoskeleton and induces acto-myosin II contractility, processes that affect cell morphology and migration. 10 During mammalian development, changes in cell morphology and positioning play important roles.…”
mentioning
confidence: 99%